(untitled) (AmeriQuests)
This paper undertakes to investigate parallels between evictions of irregularized persons in Apartheid South Africa and contemporary Europe. In both cases, people were denied the right to a home (or at least: to the home they were occupying at that moment) because they were considered to be illegal aliens. But how did this situation come about? How did these people become illegal aliens? And while it seems obvious that illegal aliens can be deported from the territory, how did their alien status come to justify the destruction of their homes? Pursuing the association means we will not only identify similarities, but also try to establish where the association meets it limits. The aim of pursuing a visual association across time and space is not primarily to draw exact parallels. In contemporary Europe, the use of violence of a “white” state in order to destroy the housing of “non-whites” is accepted as a normal element in the regulation of “non-white” populations. The association with Apartheid seeks to problematize this normality by pointing to the uneasy pedigree of such practices.